Development of double-layer metamaterial with high effective medium ratio values for S- and C-band applications - Rasheduzzaman Sifat; Mohammad Rashed Iqbal Faruque; Tayaallen Ramachandran; Mardina Abdullah; Mohammad Tariqul Islam; K.S. Al-Mugren (Heliyon, 2024)
This study introduces a compact double negative metamaterial (DNM) composed of three split rings connected slab resonator (TSRCSR) based double-layer design with a high 13.9 EMR (effective medium ratio) value. A double-layer patch is introduced to achieve the novel double negative properties, including negative behaviours of effective medium parameters, including refractive index, permittivity, and permeability with a high effective medium ratio for the miniaturised size of the introduced unconventional material that is highly suitable for microwave S and C band covering applications. The popular low-loss Rogers RT5880 (thickness 1.575 mm) substrate and copper resonator materials are utilized to develop the metamaterial unit cell that offers triple resonance between frequencies from 1 to 8 GHz. Therefore, the proposed metamaterial exhibits resonance peaks at 2.75, 5.2, and 6.3 GHz, suitable for radar, communication satellite, and long-distance telecommunication applications, respectively. The commercially available simulator known as Computer Simulation Technology (CST) is adopted to develop and simulate the 8 × 8 mm2 metamaterial design. The simulation results of the introduced TSRCSR design structure were verified by adopting the Ansys High-Frequency Structure Simulator (HFSS). Furthermore, it was then proved with the help of equivalent circuit model findings gained from the Advanced Design Structure (ADS) software. On the other hand, the analytical results were further validated by measuring the TSRCSR design utilizing a Vector Network Analyzer (VNA). These analyses become one of the novelties of this work, where the compact TSRCSR metamaterial successfully gained small discrepancies in transmission coefficient values when compared to both analytical and measurement results. The proposed metamaterial is highly suggested for communication devices for its extensive effective characteristics and compactness.